Locally confined membrane modification of sulfonated membranes for fuel cell application - Krishnan, N. Nambi; Henkensmeier, Dirk; Jang, Jong Hyun; Hink, Steffen; Kim, Hyoung-Juhn; Nam, Suk-Woo; Lim, Tae-Hoon (Elsevier BV, 2014)
We report a method which protects sulfonated hydrocarbon based proton exchange membranes at the interface between active and non-active area and in the gas inlet/outlet areas, where stresses are maximal during fuel cell operation. The sensitive membrane regions are subjected to a locally confined heat treatment using a stainless steel frame, under which clesulfonation and/or crosslinking reactions occur. While modifications in air limit the reaction temperature to 180 degrees C, inert atmosphere allows to raise the temperature and thus to shorten the necessary reaction time from 24 h to less than 30 min. Membranes are prepared from a commercially available copolymer (SES0005, Aquafone (TM)), which has a high IEC (2.08 meq g(-1)) and a water uptake of 64%. As expected, modified membranes show reduced IEC values, reduced water uptake, and increased dimensional stability. Catalyst coated membranes (CCMs) are assembled into single cells for fuel cell testing. A membrane modified on all edges shows a stable performance in H-2/air fuel cell operation and an H-2 crossover current density of 0.52 mA cm(-2), while a membrane modified only on two edges fails within 50 h. Tensile and fuel cell tests show that the interface between modified and pristine area is not the preferred breaking point. (C). 2013 Elsevier B.V. All rights reserved.